2022
DOI: 10.1051/0004-6361/202243489
|View full text |Cite
|
Sign up to set email alerts
|

Desorption of organic molecules from interstellar ices, combining experiments and computer simulations: Acetaldehyde as a case study

Abstract: Context. Explaining the presence of complex organic molecules (COMs) in interstellar environments requires a thorough understanding of the physics and chemistry occurring in the interplay between the gas phase and interstellar surfaces. Experiments and computer simulations are pivotal in building a comprehensive catalogue of processes of relevance for the build up of organic molecules in those environments. Aims. We combine experiments with tailored computer simulations to study the desorption dynamics of acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…The y found that the acetaldehyde BE on a mixture of iced water-acetaldehyde is 3079 K, substantially different from the Wakelam et al's estimate. In a very recent combined theoretical and experimental study, Molpeceres et al ( 2022 ) obtained, for the desorption of acetaldehyde on non-porous amorphous solid water surfaces, the values of 3624 and 3774 K, respecti vely. These v alues are relatively similar to the Corazzi et al's value, but still far from that of Wakelam et al's one.…”
mentioning
confidence: 99%
“…The y found that the acetaldehyde BE on a mixture of iced water-acetaldehyde is 3079 K, substantially different from the Wakelam et al's estimate. In a very recent combined theoretical and experimental study, Molpeceres et al ( 2022 ) obtained, for the desorption of acetaldehyde on non-porous amorphous solid water surfaces, the values of 3624 and 3774 K, respecti vely. These v alues are relatively similar to the Corazzi et al's value, but still far from that of Wakelam et al's one.…”
mentioning
confidence: 99%
“…This fact could be inferred from previous studies (Garrod, R. T. et al 2007;Minissale, M. et al 2016;Fredon & Cuppen 2018;Fredon et al 2021) where the efficiency of chemical desorption is a function of BE. However, as previously indicated for thermal desorption studies Ferrero et al 2022a;Molpeceres, G. et al 2022), we must emphasize that considering the whole distribution of binding sites is essential to unravel the role of non-thermal mechanisms. Here we found that the binding energy anticorrelates with the fraction of energy dissipated into the lattice and the acquired translational energy of the nascent molecule.…”
Section: Extended Samplingmentioning
confidence: 91%
“…Regarding the estimate of the desorption prefactor, it is almost absent in the abovementioned theoretical studies, often assumed to be 10 12 -10 13 (the experimental assumption or the Hasegawa et al 1992 formula). Recently, Molpeceres et al (2020Molpeceres et al ( , 2022 proposed a new method, in which they run MD at the GFN2 level for the adsorption of atoms, H 2 , and acetaldehyde on icy clusters. The prefactor, named by those authors the attempt frequency of desorption, was computed with an approach that had never been proposed in the related literature on surface science phenomena.…”
Section: Theoretical Datamentioning
confidence: 99%
“…Furthermore, a component in the COMr can also be simply due to different rotations of the whole molecule, either lying flat (small COMr) or almost perpendicular to the surface (high COMr), without any attempt to desorb. We notice that the approach of Molpeceres et al (2020Molpeceres et al ( , 2022 has never been proposed by the surface science community, even though many methods have been proposed in the last years in order to estimate the prefactor (Fichthorn & Miron 2002;Sprowl et al 2016;Rybicki & Sauer 2022). Furthermore, that procedure implies a rather long MD run, which can only be carried out with classical force fields or the GFNx level of theory, reducing the final accuracy.…”
Section: Theoretical Datamentioning
confidence: 99%